Monocyte–red blood cell crosstalk supports clearance and heme metabolism in sickle cell anemia - Borges, Marina Dorigatti; de Souza, Matheus Ajeje; Paes, Izabela Felice; Leonardo, Daniela Pinheiro; Albuquerque, Dulcinéia Martins; Lanaro, Carolina; Saad, Sara Teresinha Ollala; Sesti-Costa, Renata; Costa, Fernando Ferreira (Frontiers in Immunology, 2025)
BackgroundMonocytes can interact with erythroid cells and contribute to macrophage pools under anemic stress, thereby supporting the erythropoietic niche. In sickle cell anemia (SCA), extensive hemolysis and ineffective erythropoiesis may expose circulating monocytes to abnormal red blood cells (RBCs), potentially altering their phenotype and function to accommodate the higher erythropoietic response and iron demand.Methods and resultsWe characterized circulating monocytes from SCA patients at steady state using flow cytometry and in vitro phagocytosis assays. Intracellular RBC material was detected in all circulating monocyte subsets from SCA patients, indicating active erythrophagocytosis. Mechanistically, SCA monocytes displayed upregulated VCAM-1 and reduced SIRP-α expression, favoring RBC binding and internalization even when CD47 expression on RBCs was preserved. Following RBC engulfment, monocytes upregulated heme oxygenase-1 (HO-1) and ferroportin (FPN), consistent with enhanced heme degradation and iron export, and expressed higher levels of CD206, suggesting a regulatory phenotype. In vitro assays confirmed that both sickle RBCs and SCA monocytes synergistically promoted erythrophagocytosis.ConclusionCirculating monocytes from SCA patients undergo phenotypic and functional reprogramming upon interaction with sickled RBCs, acquiring features reminiscent of erythroblastic island macrophages. These findings highlight a previously underappreciated role for monocytes in RBC clearance, heme metabolism, and iron recycling in SCA, with potential implications for inflammation and disease progression.